2017
DOI: 10.1615/critreveukaryotgeneexpr.2017019244
|View full text |Cite
|
Sign up to set email alerts
|

Role of lncRNAs as Novel Biomarkers and Therapeutic Targets in Ovarian Cancer

Abstract: Ovarian cancer (OC) is the leading cause of death among all gynecological malignancies in the world and its underlying mechanism is still unclear. Compared with research on microRNAs, research on long non-coding RNAs (lncRNAs) is still in its infancy. Studies in recent years have demonstrated that lncRNAs exhibit multiple biological functions in various stages of OC development. In this review, we conclude that lncRNAs are closely involved in the pathogenesis of OC. The expression of lncRNAs indicates the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…8 Recently, accumulating evidences have shown that lncRNAs acted as molecular biomarkers and therapeutic targets in various cancers, including non-small-cell lung cancer, prostate cancer, and ovarian cancer. [9][10][11] In terms of GC, novel lncRNAs of v-raf murine sarcoma viral oncogene homolog B1 (BRAF)activated noncoding RNA (BANCR) 12 and HOX transcript antisense RNA (HOTAIR) 13 play a critical role in cell proliferation, metastasis, and apoptosis and are associated with clinical progression and a poor prognosis in GC. These findings clearly indicate that lncRNAs are involved in tumor biology and can be used for cancer diagnosis, prognosis, and potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, accumulating evidences have shown that lncRNAs acted as molecular biomarkers and therapeutic targets in various cancers, including non-small-cell lung cancer, prostate cancer, and ovarian cancer. [9][10][11] In terms of GC, novel lncRNAs of v-raf murine sarcoma viral oncogene homolog B1 (BRAF)activated noncoding RNA (BANCR) 12 and HOX transcript antisense RNA (HOTAIR) 13 play a critical role in cell proliferation, metastasis, and apoptosis and are associated with clinical progression and a poor prognosis in GC. These findings clearly indicate that lncRNAs are involved in tumor biology and can be used for cancer diagnosis, prognosis, and potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lncRNA‐miRNA‐mRNA regulatory axis widely participates in oesophageal carcinogenesis . Many lncRNAs play pivotal roles in maintaining and promoting the biological characteristics of tumour cells, and thus, lncRNAs may be the attractive therapeutic targets in a variety of tumours . Our recent work identified many differential lncRNA through TCGA database, and we revealed that ZEB1‐AS1 was significantly up‐regulated in ESCA, but its precise functions remain unknown.…”
Section: Introductionmentioning
confidence: 83%
“…18 Many lncRNAs play pivotal roles in maintaining and promoting the biological characteristics of tumour cells, and thus, lncRNAs may be the attractive therapeutic targets in a variety of tumours. 19,20 Our recent work identified many differential lncRNA through TCGA database, and we revealed that ZEB1-AS1 was significantly up-regulated in ESCA, 21 but its precise functions remain unknown. It is a fact that ZEB1-AS1 is closely correlated with tumour occurrence and development, such as bladder cancer, 22 glioma, 23 melanoma 24 and non-small-cell lung cancer, 25 and these data suggest that ZEB1-AS1 is involved in tumour progression via multiple different molecular mechanisms, suggesting the complexity of ZEB1-AS1 function in these tumours.…”
mentioning
confidence: 87%
“…Recent studies have shown that a variety of lncRNAs are abnormally expressed in ovarian cancer and contribute to the pathological progress of ovarian cancer [16,17]. LncRNA MALAT1 is upregulated in ovarian cancer tissues and indicates lower 5-year overall survival rate.…”
Section: Discussionmentioning
confidence: 99%